Modelling large solar proton events with the shock-and-particle model - Pomoell Jens (Journal of Space Weather and Space Climate, 2015)
We have developed a new version of a model that combines a two-dimensional Sun-to-Earth magnetohydrodynamic (MHD) simulation of the propagation of a CME-driven shock and a simulation of the transport of particles along the interplanetary magnetic field (IMF) line connecting the shock front and the observer. We assume that the shock-accelerated particles are injected at the point along the shock front that intersects this IMF line, i.e. at the cobpoint. Novel features of the model are an improved solar wind model and an enhanced fully automated algorithm to extract the necessary plasma characteristics from the shock simulation. In this work, the new algorithms have been employed to simulate the 2000 April 4 and the 2006 December 13 SEP events. In addition to quantifying the performance of the new model with respect to results obtained using previous versions of the shock-and-particle model, we investigate the semi-empirical relation between the injection rate of shock-accelerated particles, Q, and the jump in speed across the shock, VR, known as the Q(VR) relation. Our results show that while the magnetic field and density compression at the shock front is markedly different than in our previous modeling, the evolution of VR remains largely similar. As a result, we confirm that a simple relation can still be established between Q and VR, which enables the computation of synthetic intensity-time profiles at any location in interplanetary space. Furthermore, the new shock extraction tool is found to yield improved results being in general more robust. These results are important not only with regard to efforts to develop coupled magnetohydrodynamic and particle simulation models, but also to improve space weather related software tools that aim to predict the peak intensities, fluences and proton intensity-time profiles of SEP events (such as the SOLPENCO tool).